2010
DOI: 10.1016/j.actamat.2009.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of indium antimonide between −176°C and 400°C under hydrostatic pressure. Part II: Microscopic aspects of the deformation

Abstract: Indium antimonide (InSb) has been plastically deformed over a wide temperature range, from 400 down to À176°C (see the companion paper: Kedjar B, Thilly L, Demenet JL, Rabier J. Acta Mater 2009) and transmission electron microscopy was used to characterize the deformation microstructures. In the ductile regime, i.e. T > T tr1 % 150°C, the crystal deforms via the nucleation and motion of perfect dislocations belonging to the glide set. In the brittle domain, i.e. for T < T tr1 % 150°C, two regimes are observed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Further experiments would now be performed at intermediate temperatures to correlate precisely the apparition of the BDT with an abrupt or gradual change of plasticity mechanism as in the case of semi-conductor1213.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further experiments would now be performed at intermediate temperatures to correlate precisely the apparition of the BDT with an abrupt or gradual change of plasticity mechanism as in the case of semi-conductor1213.…”
Section: Discussionmentioning
confidence: 99%
“…While the high temperature response of MAX phases was supposed to be only based on temperature dependent grain boundary decohesion and/or interplanar delamination stress 17 , the present work provides new elements through the observation of cross slip events. Further experiments would now be performed at intermediate temperatures to correlate precisely the apparition of the BDT with an abrupt or gradual change of plasticity mechanism as in the case of semi-conductor 12 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1950s, numerous studies were conducted to understand plasticity mechanisms in the different semiconductor materials and it is now widely accepted that the occurrence of the BDT is associated to a change in the nature of the dislocations 1 , 2 . Traditionally, investigation of the plasticity of brittle materials, in the form of bulk single crystals or polycrystals, requires the use of a deformation technique imposing a hydrostatic pressure component to prevent/delay fracture to the benefit of plasticity 3 6 . In such conditions favorable to plasticity, it has been shown that the Shuffle–Glide transition plays a major role in the BDT of semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Since then it has been shown that high stress and low temperatures perfect shuffle dislocations are found to control plasticity below the usual BDT (brittle to ductile transition temperature) in silicon whereas dissociated glide dislocations control the low stress high temperature regime 2. This has been found to be quite a general property of the plasticity of semiconductors materials 3, 4. In this context dislocation characteristics in diamond have to be re‐investigated, especially for dislocations resulting from deformation conditions close to the BDT, having in mind that special core structures can be present in diamond.…”
Section: Introductionmentioning
confidence: 99%